TELAAH HERMENEUTIKA HANS-GEORG GADAMER; MENUJU PENDEKATAN INTEGRATIF DALAM STUDI ISLAM - Thahir, Lukman S.; Dawing, Darlis (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
The hermeneutic approach was rejected by some Muslim scholars because it came from the West, but some other scholars actually tried to lend the theory in understanding the Qur’an and hadith. Not only because of the contribution to Islamic studies, but this approach has very strong roots in Islam itself. This paper shows the possibility of applying hermeneutic methods, especially Hans-Georg Gadamer’s circle hermeneutics in understanding religious texts. This paper also explores the contemporary Muslim perspective and the classical position of hermeneutic approach. This data shows that circular hermeneutics is a new term in Islamic thought but has existed since early times such as the time of the prophets, companions and successors known as ta`wil. This shows that there are several hermeneutic theories that can be applied in understanding the Qur’an and hadith. Classical sciences, such as ulumul Qur’an, ulumul hadith and ushul fiqh can be strengthened by a hermeneutic approach towards a more comprehensive and contextual understanding.